PROSES BERPIKIR DALAM MEMECAHKAN MASALAH BERDASARKAN TINGKAT KEMAMPUAN MATEMATIKA PADA SISWA KELAS VIII SMP - Evaritus Janggu; Gregorius Taga; Agustina Mei (Program Studi Pendidikan Matematika, 2023)
This study aims to determine the thinking process of students with high, medium and low abilities in solving mathematical problems in the Material of a Two-variable Linear Equation System using Polya theory for class VIII SMP Bina Kusuma in the academic year 2022/2023. Each student has different abilities so the teacher can choose a variety of learning methods according to the student's ability level. The approach used is a qualitative approach. The research subjects were 6 students of class VIII SMP Bina Kusuma Ruteng. Data collection in this study was carried out through tests, interviews and documentation with the research instruments, namely the first-semester report cards of mathematical abilities, problem-solving tests and interviews. The data analysis used is the data analysis model of Miles and Huberman, namely, data collection, data reduction, data presentation and concluding. The results of the analysis of research data show that conceptual thinking processes are only owned by students with high mathematical abilities, while semi-conceptual thinking processes only occur in students with moderate mathematical abilities, and computational thinking processes only occur in students with low mathematical abilities.